Pengaruh Motivasi dan Seleksi Terhadap Pengembangan Karir Karyawan PT Harapan Jaya Pangan - Giovanna Lodeva; Syawaluddin Syawaluddin; Mila Asmawiani Okta; Thomas Sumarsan Goh (Universitas Batanghari Jambi, 2022)
Employees who have worked certainly have targets and goals, one of which is: realizing their career plans. The company is responsible for the continuity of the employee's career so that in this case the company also continues to make efforts to maintain productivity, effectiveness and efficiency, the efforts made by the company to ensure that employees maintain their qualifications according to the company's strategic planning. Employee work motivation is important to note because it is able to encourage employees to develop creativity and mobilize their abilities and efforts in order to achieve career plans and the job selection process must be carried out as well as possible in order to produce employees who have qualified skills and abilities. The purpose of this study was to determine the effect of motivation and selection on the career development of employees of PT. Harapan Jaya Pangan. The research method used is a survey approach analysis method, the type of research is quantitative descriptive, the research method is carried out by questionnaires, interviews, and documentation studies. The analytical method used is multiple linear regression. The population is employees of PT. Harapan Jaya Pangan. The sample in the study to be tested amounted to 66 people. The data analysis technique used is the reliability validity test, the classical assumption test, the coefficient of determination (R2) test, multiple regression analysis, and hypothesis testing. The results of this study indicate that motivation and selection simultaneously affect the career development of employees of PT. Harapan Jaya Pangan. The selection variable partially has a significant effect on career development while motivation partially has no effect on career development. motivation and selection explain their influence on the career development of employees of PT. Harapan Jaya Pangan with a coefficient of determination of 0.618, which means that 61.8% of career development variables can be explained by motivation and selection variables and the remaining 38.2% is varied by other factors not examined such as organizational culture, work discipline, job satisfaction and so on